FeSe-based superconductors with a superconducting transition temperature of 50 K. (5th December 2018) - Shi, M Z; Wang, N Z; Lei, B; Ying, J J; Zhu, C S; Sun, Z L; Cui, J H; Meng, F B; Shang, C; Ma, L K; Chen, X H
Abstract: Due to the strong reactivity of alkaline metals and the easy formation of the impurity phase, the superconducting transition temperature ( T c ) of alkaline metals intercalated FeSe is usually limited to 45 K. To avoid the formation of impurity and improve the T c, we intercalate a more chemically inert organic ion (rather than the chemically reactive alkaline metals) into FeSe single crystal in this report. A new FeSe-based superconductor, namely (TBA)0.3 FeSe, with T c of 50 K, is synthesized by intercalating FeSe single crystal with organic ion tetrabutyl ammonium (TBA + ) via an electrochemical intercalation method, which has the highest T c among FeSe-based bulk superconductors. The structure of the organic ion intercalated product consists of the alternate stacking of monolayer FeSe and the organic molecule. The superconductivity of (TBA)0.3 FeSe is confirmed by both the magnetic susceptibility and the transport measurement. It is suggested that the chemically inert organic ion should play a key role in the enhancement of T c by avoiding the formation of impurity and disorder in FeSe plane as possible. We also suggest that the TBA + intercalated FeSe with well defined shape and higher T c offer a good playground for further bulk measurement investigation.